Synthesis and Characterization of a Porous Ga2O3 Material with a Low Dielectric Constant - Dong, Xue; Woo, Chaeheon; Yoo, Chan Sei; Kim, Tae Yeong; Zhang, Xiaojie; Kim, Yeongjin; Kang, Jinsu; Jeon, Jiho; Bang, Hyeon Seok; Kim, Youngho; Park, Jae Hyuk; Yu, Hak Ki; et al. (Crystal Growth and Design, 2024)
In the context of contemporary wireless communication technologies, operational frequencies have considerably escalated. Consequently, the demand for dielectric ceramics with low dielectric constants and minimal losses has become imperative in the field. Thermally stable β-Ga2O3 was synthesized by a simple chemical precipitation route followed by calcination, making it a promising candidate for microwave applications. The as-prepared β-Ga2O3 maintained a pore structure with a width of 20.943 nm. Notably, the material exhibited early-stage sintering at relatively low temperatures, around 900 °C, due to these pores. The as-prepared β-Ga2O3 ceramics exhibited outstanding dielectric properties, featuring a lower ϵr value of 3.2168 and a low dielectric loss of 0.000795 at 9.4 GHz. The lower ϵr contributes to minimized time delays, while the low dielectric loss enhances the signal selectivity. These findings establish β-Ga2O3 as a suitable material for electronic packaging in microwave applications.
Keywords: Dielectric ceramic; Low dielectric constants; Low dielectric loss; Microwave applications; Operational frequency; Simple++; Synthesis and characterizations; Synthesised; Thermally stable; Wireless communication technology